Bargaining regimes and wages in Portugal - Hartog, Joop (2018)
In this paper we analyse the bargaining regime wage-effect in Portugal. The results indicate that the bargaining regime coverage is important in explain- ing the variability of wages. Wage differentials between bargaining regimes are substantial, a fact which may be related to a decentralised wage setting which pre- vails in Portugal. The highest wages are generated by multi-firm negotiations and the lowest are generated by sectoral contracts. Single-firm contracts align at an intermediate level in the ranking.